Hubungan Adiksi Smartphone dengan Kecemasan Sosial Pada Siswa-Siswi SMP Negeri 1 Kota Kupang - Darling Adelaide Julietta Miha Raja; Regina Marvina Hutasoit; Nicholas Edwin Handoyo; Efrisca Meliyuita Br. Damanik (Malahayati Nursing Journal, 2026)
ABSTRACT The increasing use of smartphones among adolescents has the potential to lead to addiction, which may affect their ability to cope with social situations and trigger social anxiety. In Kupang City, smartphones serve as the primary medium for adolescents to communicate and access entertainment, resulting in high usage intensity. This condition highlights the need to examine the relationship between smartphone addiction and social anxiety among adolescents in this setting.  This study sought to examine the relationship between smartphone addiction levels and social anxiety levels among students of SMP Negeri 1 Kupang in 2025. This quantitative observational analytic study with a cross-sectional design was conducted at SMP Negeri 1 Kupang. A total of 88 students from grades VIII and IX were selected using cluster sampling. Smartphone addiction was evaluated using the Smartphone Addiction Scale–Short Version (SAS-SV), whereas social anxiety was measured with Liebowitz Social Anxiety Scale–Self Report (LSAS-SR The relationship between variables was examined using Spearman’s rank correlation test at a 5% significance level (p 0.05). Smartphone addiction was predominantly in the moderate category (53.4%), while social anxiety was most frequently classified as mild (22.7%). Spearman’s rank correlation test showed a positive association of moderate strength between smartphone addiction and social anxiety (r = 0.512; p 0.001). There is a significant relationship between smartphone addiction and social anxiety among students of SMP Negeri 1 Kupang in 2025.  Keywords: Smartphone Addiction, Social Anxiety, Adolescents, Kupang City.  ABSTRAK Meningkatnya penggunaan smartphone pada remaja berpotensi menimbulkan adiksi yang dapat memengaruhi kemampuan mereka menghadapi situasi sosial, termasuk memicu kecemasan sosial. Di Kota Kupang, smartphonemenjadi media utama bagi remaja dalam berkomunikasi dan mengakses hiburan, sehingga intensitas penggunaannya cenderung tinggi. Kondisi tersebut mendorong perlunya penelitian mengenai hubungan antara adiksi smartphone dan kecemasan sosial pada remaja di wilayah ini.   Penelitian ini bertujuan untuk mengkaji hubungan antara tingkat adiksi smartphone dengan tingkat kecemasan sosial pada siswa-siswi SMP Negeri 1 Kota Kupang tahun 2025. Penelitian ini menggunakan pendekatan kuantitatif dengan desain observasional analitik cross-sectional, yang dilaksanakan di SMP Negeri 1 Kupang, dengan jumlah sampel 88 siswa-siswi kelas VIII dan IX dipilih dengan metode cluster sampling. Tingkat adiksi smartphone diukur menggunakan kuesioner Smartphone Addiction Scale–Short Version (SAS-SV) dan tingkat kecemasan sosial diukur menggunakan kuesioner Liebowitz Social Anxiety Scale–Self Report (LSAS-SR). Analisis hubungan dinilai menggunakan uji korelasi Rank Spearman dengan taraf signifikansi 5% (p 0,05). Tingkat adiksi smartphone didominasi kategori sedang (53,4%), sedangkan tingkat kecemasan sosial paling banyak pada kategori ringan (22,7%). Uji korelasi Rank Spearman menunjukkan hubungan positif dengan kekuatan sedang antara tingkat adiksi smartphone dan tingkat kecemasan sosial (r = 0,512; p0,001).  Terdapat hubungan yang signifikan antara adiksi smartphone dengan kecemasan sosial pada siswa-siswi SMP Negeri 1 Kota Kupang tahun 2025. Kata Kunci: Adiksi Smartphone, Kecemasan Sosial, Remaja, Kota  Kupang.